2019
DOI: 10.1002/ecy.2859
|View full text |Cite
|
Sign up to set email alerts
|

Global change stressors alter resources and shift plant interactions from facilitation to competition over time

Abstract: Global change stressors such as drought and plant invasion can affect ecosystem structure and function via mediation of resource availability and plant competition outcomes. Yet, it remains uncertain how native plants respond to drought stress that co-occurs with potentially novel resource conditions created by a nonnative invader. Further, there is likely to be temporal variation in competition outcomes between native and nonnative plant species depending on which resources are most limiting at a given time. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(39 citation statements)
references
References 75 publications
1
37
1
Order By: Relevance
“…For example, Alba et al . (2019) demonstrated that the interaction effect of drought and the invasive grass I . cylindrical shifted unexpectedly from facilitation to competition over time.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Alba et al . (2019) demonstrated that the interaction effect of drought and the invasive grass I . cylindrical shifted unexpectedly from facilitation to competition over time.…”
Section: Introductionmentioning
confidence: 99%
“…One of important global change factors is the introduction of species to areas outside their historic geographic ranges (Alba, Fahey, & Flory, 2019; van der Putten, 2012). Species that spread rapidly may not be well adapted to their new geographic ranges or to the species in their new communities (Allen et al, 2017; Zhang, Pennings, Li, & Wu, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its C 4 pathways, it can be drought tolerant, adapted to high temperatures, and also have greater water use efficiency, making it potentially more competitive in lower latitudes as compared to C 3 invaders. Since its initial introduction to the United States, cogongrass has expanded its range in the southeastern United States from Texas to Florida and as far north as Virginia (Jose et al 2002) and it is considered a primary threat to biodiversity and ecosystem functions (Estrada and Flory 2015, Fahey et al 2018, Alba et al 2019.…”
Section: Methodsmentioning
confidence: 99%
“…The watering frequency was modified according to the watering frequency used in Webster and Grey (2008) to have a close representation of the weather in Florida, which also resulted in similar soil water contents to what Burns (2004) used in her study. Indeed, a further lower water level could be used to mimic a stronger drought (Burns 2004, Alba et al 2019. Our watering frequency was designed based on a comprehensive consideration of watering period and soil water content to have a close representation of the weather in Florida, which also aimed to mimic meteorological drought to ultimately show vegetation physiological drought response.…”
Section: Experimental Designmentioning
confidence: 99%